An Adaptation of the MacArthur-Bates CDI in 17 Arabic Dialects for Children Aged 8 to 30 Months. Issue 4 (2nd October 2021) - Abdelwahab, Alshaimaa Gaber Salah; Forbes, Samuel; Cattani, Allegra; Goslin, Jeremy; Floccia, Caroline
ABSTRACT: Assessing a child's language in the early years is critical to plan for an early intervention and maximize their learning potential. In a unique pan-Arabic approach to language development, we developed a new Arabic assessment tool, usable by parents and Early Years professionals to screen vocabulary in children between 8 months and 30 months across 17 Arab countries. Departing from the two relevant original Communicative Development Inventory forms (CDI: Words and Gestures and CDI: Words and Sentences, Fenson, Marchman, Thal, Reznick, & Bates, 2007 ), our Arabic CDI focuses on Words Only (Short Form), and assesses comprehension and production of a list of 100 words in 17 main dialects or Arabic, through a parental report. Data were collected from 436 Egyptian children and 168 children from the remaining 16 countries. Quasi-binomial model fits on Egyptian and Other Dialects comprehension and production data showed that Egyptian vocabulary norms could be reasonably extrapolated to the Other Dialects sample, as a first indication that the tool might be usable across the different countries.